2006
DOI: 10.1074/jbc.m602389200
|View full text |Cite
|
Sign up to set email alerts
|

c-Abl Interacts with the WAVE2 Signaling Complex to Induce Membrane Ruffling and Cell Spreading

Abstract: The Wiskott-Aldrich syndrome-related protein WAVE2 promotes Arp2/3-dependent actin polymerization downstream of Rho-GTPase activation. The Abelson-interacting protein-1 (Abi-1) forms the core of the WAVE2 complex and is necessary for proper stimulation of WAVE2 activity. Here we have shown that the Abl-tyrosine kinase interacts with the WAVE2 complex and that Abl kinase activity facilitates interaction between Abl and WAVE2 complex members. We have characterized various interactions between Abl and members of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
91
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 77 publications
(101 citation statements)
references
References 31 publications
4
91
0
Order By: Relevance
“…Leng and colleagues (30) reported that Tyr-150 is the only tyrosine residue to be phosphorylated in WAVE2 by c-Abl. Phosphorylation of WAVE2 by c-Abl was also shown to stimulate membrane ruffling and cell spreading, suggesting that WAVE2 might be an effector of the c-Abl kinase to regulate cytoskeletal remodeling in vivo (25). Here we show that the c-Abl-mediated phosphorylation of WAVE3 also results in the stimulation of lamellipodia formation and cell migration, which clearly supports the hypothesis that WAVE3 is also a downstream effector of c-Abl.…”
Section: Discussionsupporting
confidence: 74%
See 3 more Smart Citations
“…Leng and colleagues (30) reported that Tyr-150 is the only tyrosine residue to be phosphorylated in WAVE2 by c-Abl. Phosphorylation of WAVE2 by c-Abl was also shown to stimulate membrane ruffling and cell spreading, suggesting that WAVE2 might be an effector of the c-Abl kinase to regulate cytoskeletal remodeling in vivo (25). Here we show that the c-Abl-mediated phosphorylation of WAVE3 also results in the stimulation of lamellipodia formation and cell migration, which clearly supports the hypothesis that WAVE3 is also a downstream effector of c-Abl.…”
Section: Discussionsupporting
confidence: 74%
“…Treatment of MDA-MB-231 cells with STI-571, a specific inhibitor of c-Abl kinase activity, or expression of a kinase-dead Abl, inhibited the c-Abl-mediated phosphorylation of WAVE3, without abrogating their interaction, but resulted in a significant decrease in cell migration, clearly suggesting that the c-Abl-mediated phosphorylation of WAVE3 might be critical for the activity of WAVE3 in promoting cell migration. The interaction between c-Abl and the other members of the WAVE family of proteins has already been reported to involve the SH3 domain of c-Abl and the proline-rich domain of the WAVE proteins (25,32,35). The WAVE3-Abl interaction is more likely to involve the same region in WAVE3, because the proline-rich domain is very conserved among the WAVE proteins (5).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The inhibitory-complex component Abi1 plays a central role in WAVE2 phosphorylation (Innocenti et al, 2004), because it acts as a bridge between WAVE2 and Abl (Leng et al, 2005;Stuart et al, 2006), allowing Abl to phosphorylate WAVE2 in response to PDGF or to adhesion to fibronectin (Fig. 3A).…”
Section: Abl-family Kinases Activate Wasp and Wave Proteinsmentioning
confidence: 99%